CONFAEB e suas concepções em processo de 2001 a 2010 - Aquino, Adriana Carla de (2012)
This dissertation titled "CONFAEB and Its concepts in process from 2001 to 2010" aims to analyze the concepts discussed in the Congress of the Federation / Art Educators of Brazil - CONFAEB - in the period from 2001 to 2010. The period of analysis was thus established by the systematic occurrence of congress and the systematic presence of the researcher to congress occurred during this decade. Conceptions are in the process because they are discussed from different perspectives and in different conferences Federation / Art Educators of Brazil - FAEB. The data collection instruments were used in this thesis documentary research (the annals from 2001 to 2010 and the official program of CONFAEBs), the questionnaire, structured interview the coordinators of CONFAEBs conducted between 2001 and 2010. Discourse Analysis (ORLANDI, 1999) allowed us to understand the concepts of Art Education and the concepts that guide CONFAEBs 2001 to 2010. The instruments of data collection and the analysis of this material, organized mainly in the form of analytical tables were possible to discern the concepts implied in the speech utterance in CONFABs in the period surveyed. However the analysis of semi-structured interviews enabled realize that there is a gap between the concepts of implicit and explicit in the documents resulting from CONFAEBs and may conclude on the need to expand the research to deepen the themes addressed in Congress to broaden the understanding of the thinking of art / Brazilian educators tied to FAEB.